2001
DOI: 10.13031/2013.6120
|View full text |Cite
|
Sign up to set email alerts
|

Stream Nutrient Retention in Three Northeastern Oklahoma Agricultural Catchments

Abstract: ABSTRACT. Stream nutrient retention was examined in three adjacent agricultural catchments (Cherokee Creek, Cloud Creek, and Dry Creek)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
(53 reference statements)
8
35
0
Order By: Relevance
“…This research, with the exception of Alexander et al (2000), has been conducted in forested headwater streams with low instream NO { 3 concentrations. Our study and other research in agricultural headwater streams have indicated that these particular streams are ineffective at N removal because of NO { 3 saturation (Haggard et al 2001;Royer et al 2004;Bernot et al 2006). Studies in a variety of stream types have identified several factors to be important in removing N, such as organic carbon supply (Groffman et al 2005), NO { 3 concentration (Bernot et al 2006;Gü cker and Pusch 2006;Herrman et al 2008), ratio of depth to HRT (Seitzinger et al 2002), discharge (Peterson et al 2001), stream depth (Alexander et al 2000), and relative transient storage (Valett et al 1996).…”
Section: Discussionmentioning
confidence: 48%
“…This research, with the exception of Alexander et al (2000), has been conducted in forested headwater streams with low instream NO { 3 concentrations. Our study and other research in agricultural headwater streams have indicated that these particular streams are ineffective at N removal because of NO { 3 saturation (Haggard et al 2001;Royer et al 2004;Bernot et al 2006). Studies in a variety of stream types have identified several factors to be important in removing N, such as organic carbon supply (Groffman et al 2005), NO { 3 concentration (Bernot et al 2006;Gü cker and Pusch 2006;Herrman et al 2008), ratio of depth to HRT (Seitzinger et al 2002), discharge (Peterson et al 2001), stream depth (Alexander et al 2000), and relative transient storage (Valett et al 1996).…”
Section: Discussionmentioning
confidence: 48%
“…Ammonium accounted for 12 to 47% of the DIN load during the study period, averaging 21% of the total DIN pool. This ratio of NH 4 1 /DIN is 2 to 53 times higher than in other agricultural watersheds (Haggard et al, 2001;Royer et al, 2004). The high ratio of NH 4 1 to NO 3 2 in the Southwest Creek stream network and the generally higher rates of NH 4 1 uptake than NO 3 2 in streams (Webster et al, 2003) demonstrate the importance of NH 4 1 as a N source to riverine biota in this watershed.…”
Section: Nutrient Uptake Modeling and Measurementmentioning
confidence: 66%
“…Whereas many studies have documented increases in nutrient concentration with agricultural development (e.g., Harding et al 1999), only a few (e.g., Haggard et al 2001;Niyogi et al 2004;Bernot et al 2006) have examined how nutrient dynamics change in response to land-use intensification. Furthermore, the latter studies examined only whole-stream changes in nutrient uptake.…”
mentioning
confidence: 99%